Waiting for Godot? Welfare Attitudes in Portugal Before and After the Financial Crisis - Vieira, Mónica Brito (2017)
Do attitudes towards the welfare state change in response to economic crises? Addressing this question is sometimes difficult because of the lack of longitudinal data. This article deals with this empirical challenge using survey data from the 2008 European Social Survey and from our own follow-up survey of Spring 2013 to track welfare attitudes at the brink and at the peak of the socio-economic crisis in one of the hardest hit countries: Portugal. The literature on social policy preferences predicts an increased polarization in opinions towards the welfare state between different groups within society – in particular between labour market insiders and outsiders. However the prediction has scarcely been tested empirically. A notoriously dualized country, Portugal provides a critical setting in which to test this hypothesis. The results show attitudinal change and this varies according to labour market vulnerability. However, we observe no polarisation and advance alternative explanations for why this is so.